MATRIARKI DAN HIDDEN WOMEN DALAM SYAIR DAMARWULAN - Susanto, Dwi (ATAVISME, 2007)
The story of Damarwulan was a popular story. The reception toward this story was various. Syair, hikayat, legendriya, serat, and performance found at Javanist. Toe Syair of Damarwulan ML 176 appears many characteristics. The reading of this syair discovered much suspicious about the position of Queen of Majapahit, Kenconowungu. This paper explores matriarchal and hidden women into Syair Damarwulan. This paper used feminist perspective to explore matriarchal and hidden women. This paper has concluded that the process of matriarchal was always followed by hidden women. Relation of Queen Kenconowungu Menakjinggo and Damarwulan was one of several evidence. The presence of Damarwulan as a hero and image of idol man was the end ? of process hidden women